2002
DOI: 10.1016/s1534-5807(02)00185-5
|View full text |Cite
|
Sign up to set email alerts
|

SRC-1 and Wnt Signaling Act Together to Specify Endoderm and to Control Cleavage Orientation in Early C. elegans Embryos

Abstract: In early C. elegans embryos, signaling between a posterior blastomere, P2, and a ventral blastomere, EMS, specifies endoderm and orients the division axis of the EMS cell. Although Wnt signaling contributes to this polarizing interaction, no mutants identified to date abolish P2/EMS signaling. Here, we show that two tyrosine kinase-related genes, src-1 and mes-1, are required for the accumulation of phosphotyrosine between P2 and EMS. Moreover, src-1 and mes-1 mutants strongly enhance endoderm and EMS spindle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
232
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(263 citation statements)
references
References 39 publications
25
232
0
Order By: Relevance
“…Forward and reverse genetic screens identified components of Wnt, MAPK, and Src signaling pathways as being required for endoderm formation (Lin et al 1995;Kaletta et al 1997;Rocheleau et al 1997Rocheleau et al , 1999Meneghini et al 1999;Peters et al 1999;Schlesinger et al 1999;Shin et al 1999;Bei et al 2002;Thorpe and Moon 2004;Walston et al 2004;Huang et al 2007;Phillips et al 2007). Wnt pathway components functioning in endoderm induction include MOM-1/Porcupine, MOM-2/Wnt, MIG-14/ Wntless (a.k.a.…”
Section: P2/ems Signaling In Embyonic Endoderm Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forward and reverse genetic screens identified components of Wnt, MAPK, and Src signaling pathways as being required for endoderm formation (Lin et al 1995;Kaletta et al 1997;Rocheleau et al 1997Rocheleau et al , 1999Meneghini et al 1999;Peters et al 1999;Schlesinger et al 1999;Shin et al 1999;Bei et al 2002;Thorpe and Moon 2004;Walston et al 2004;Huang et al 2007;Phillips et al 2007). Wnt pathway components functioning in endoderm induction include MOM-1/Porcupine, MOM-2/Wnt, MIG-14/ Wntless (a.k.a.…”
Section: P2/ems Signaling In Embyonic Endoderm Inductionmentioning
confidence: 99%
“…MOM-3), MOM-5/Fz, DSH-2/ Dsh, MIG-5/Dsh, KIN-19/CK1, GSK-3/GSK3b, APR-1/APC, WRM-1/b-catenin, SYS-1/b-catenin, and POP-1/TCF, while the MAPK signaling factors are TAP-1/TabAB1, MOM-4/TAK, and LIT-1/NLK Rocheleau et al 1999;Shin et al 1999). The Tyr kinase receptor MES-1 and the Src homolog SRC-1 also participate in endoderm induction, but their role is less clear and they are not considered here (Bei et al 2002;Zhang et al 2008;Sugioka and Sawa 2010;Sumiyoshi et al 2011). Mutations or RNAi reduction of function for these Wnt and MAPK pathway genes, with the exception of pop-1/TCF, leads to a Mom phenotype (more mesoderm), in which EMS divides symmetrically to give two MS-like daughters (Fig.…”
Section: P2/ems Signaling In Embyonic Endoderm Inductionmentioning
confidence: 99%
“…P2/EMS signaling involves two redundant pathways that act in parallel to rotate the spindle apparatus in EMS and to specify the endoderm fate: a mom-2/mom-5 Wnt ligand/Frizzled (Fz) receptor cascade and a second pathway consisting of the tyrosine-kinase related genes mes-1 and src-1 c-Src (Bei et al 2002). To examine whether mom-2/mom-5 or mes-1/src-1 pathways promote the asymmetric localizations of GPR-1/GPR-2 and LIN-5, we examined embryos mutant for components of one of the two pathways.…”
Section: Asymmetric Localization Of Gpr-1/gpr-2 Correlates With Spindmentioning
confidence: 99%
“…Its simplicity, the stereotyped cell lineage, and cell movements pattern, together with its transparency, make this animal an ideal model for studying development. Genetic studies, in combination with 4D microscopy analyses, have shown that CED‐10/Rac is required for proper rotation of the mitotic spindle of some early blastomeres in the C. elegans embryo, named EMS − the endoderm and mesoderm precursor – and ABar − whose descendants form part of the pharynx − 15, 16. These mitotic spindle orientations are induced by cell signaling, from blastomeres derived from the posterior cell at the two‐cell stage embryo − termed P1 −, that triggers actin cytoskeletal reorganizations in the target cells.…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%